Overview of the Characteristics of Tax Haven - Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2023)
Tax havens have become a subject of great interest among policymakers, scholars and the general public, and are central to many important current policy debates. This chapter provides an overview of the scholarly literature on the characteristics and origins of tax havens. The earlier literature, used cross-country analysis and found evidence that tax havens tend to have stronger governance institutions than comparable nonhaven countries. The more recent literature analyses the historical origins of tax havens and undertakes longitudinal analysis of their adoption of haven-like laws. This chapter also presents a descriptive analysis of the relationship between tax haven status and quantitative measures of countries' historical characteristics. This descriptive analysis suggests that tax haven jurisdictions are not appreciably different from nonhavens in their historical experience of foreign rule and in other historical characteristics. This suggests some caution in attributing tax havens' status to their colonial history or to other historical variables.
Keywords: H87; O10; 330; tax havens; international taxation; colonial history; governance; economic development; comparative economics